Analisis Tingkat Kepuasan Mahasiswa Profesi Ners Selama Pembelajaran Klinis di Masa Pandemi Covid-19 - Sidaria Sidaria; Dewi Murni; Ilfa Khairina; Nelwati Nelwati (Universitas Batanghari Jambi, 2022)
Hybrid learning during the Covid-19 pandemic was also applied to clinical practice of undergraduate nursing students. The policy of limiting practice hours and the guidance process is mostly done online. With these changes, it is necessary to measure student satisfaction. Student satisfaction in clinical practice is important to achieve optimal learning objectives. The purpose of this study was to determine the level of satisfaction of undergraduate nursing students during clinical learning in the Covid-19 pandemic. Quantitative design was used with descriptive study. The research sample was undergraduate nursing students who were taken using the total population technique, the number of samples was 81. Data were collected using the CLES+T questionnaire. Data analysis was performed univariately. The level of satisfaction of undergraduate nursing students during clinical learning in the Covid-19 pandemic was 49.4 % satisfied and 40.7 % very satisfied, leadership style of The ward manager dimension was 53.1 % very satisfied, role of the Nurse teacher dimension was 48.1 % very satisfied, premises of nursing on The Ward was 43.2 % very satisfied, supervisory relationship was 40.7 % very satisfied, pedagogical atmosphere was 35.8 % very satisfied. The majority of the satisfaction levels of undergraduate nursing students during clinical learning in the Covid-19 pandemic are satisfied and very satisfied. The leadership style of the ward manager dimension is the most very satisfied.